ECOLOGICAL-GEOGRAPHICAL AND MORPHOLOGICAL-ANATOMICAL FEATURES OF SCUTELLARIA SIEVERSII BUNGE IN THE ILE-ALATAU CONDITIONS (Eurasian Journal of Ecology, 2026)
The study identified the ecological and geographical patterns of distribution of Scutellaria sieversii Bunge within the Ile Alatau range, as well as the species’ adaptation to the mountain conditions of the Northern Tien Shan, using its morpho-anatomical characteristics as a structural basis.Data were collected from various ecotopes of natural populations; field observations, GIS visualization of localities, and herbarium specimens were employed. The anatomical structure of the leaf, stem, and root was examined on cross-sections prepared with a microtome after fixation in 60–70% ethanol, followed by microphotography and biometric measurements. In Kazakhstan, this species was found to be clearly confined to the mountain and submountain zones. Within the Ile Alatau, it forms an elongated but fragmented distribution belt extending mainly along the northern and northwestern macro-slopes of the middle mountain belt. Its localities are associated with well-drained rocky and gravelly substrates, while the species avoids excessively moist valleys and areas subjected to intensive anthropogenic transformation. Morphological traits exhibit high plasticity (plant height 12–40 cm; variable leaf and bud size), whereas generative structures are more stable (corolla length 2.5–3.7 cm). Anatomical and biometric data demonstrate a combination of xero- and mesomorphic features: a well-developed cuticle and leaf pubescence, distinct mesophyll, mechanical elements in the stem, and a strong cortical zone of the root with protective periderm and well-balanced conductive tissues characterized by dominant xylem.  The obtained results confirm the formation of a comprehensive adaptive complex in S. sieversii, ensuring resistance to high insolation, periodic moisture deficiency, and microclimatic heterogeneity of mountain ecosystems. These findings may be applied in further ecological-anatomical and conservation studies.Keywords: Scutellaria sieversii; Ile Alatau; Northern Tien Shan; ecological and geographical distribution; GIS analysis; populations; morphological plasticity; leaf anatomy; stem anatomy; root anatomy; xeromorphic traits; adaptation to aridity.